2015
DOI: 10.1016/j.msec.2014.10.055
|View full text |Cite
|
Sign up to set email alerts
|

New poly(ester urea) derived from l-leucine: Electrospun scaffolds loaded with antibacterial drugs and enzymes

Abstract: Electrospun scaffolds from an amino acid containing poly(ester urea) (PEU) were developed as promising materials in the biomedical field and specifically in tissue engineering applications. The selected poly(ester urea) was obtained with a high yield and molecular weight by reaction of phosgene with a bis(α-aminoacyl)-α,ω-dioldiester monomer. The polymer having L-leucine, 1,6-hexanediol and carbonic acid units had a semicrystalline character and relatively high glass transition and melting temperatures. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…49 However, some proteins withstand both denaturation factors and retain their functionality aer electrospinning. These proteins include insulin, 50 chondroitinase, 9 lysozyme, 51,52 chymotrypsin, 53,54 and others.…”
Section: Bsa Release From the Blended Matsmentioning
confidence: 99%
“…49 However, some proteins withstand both denaturation factors and retain their functionality aer electrospinning. These proteins include insulin, 50 chondroitinase, 9 lysozyme, 51,52 chymotrypsin, 53,54 and others.…”
Section: Bsa Release From the Blended Matsmentioning
confidence: 99%
“…The polymer is characterized by a melting temperature of 114 • C, a glass transition temperature of 47 • C, and a tensile strength at yield, elongation at break, and Young's modulus of 21 MPa, 114%, and 622 MPa, respectively. Previous works indicated that the polymer could be electrospun into micro/nanofibers loaded with antibacterial drugs [36]. Furthermore, hybrid electrospun scaffolds constituted of a mixture poly(3-thiophene methyl acetate) and a copolymer based on 1L6 showed promising conductive and biodegradable properties [37].…”
Section: Introductionmentioning
confidence: 99%
“…Probably, electrospinning technique constitute an ideal process to render materials for the study of antibacterial properties due to its versatility and the ability to load agents with different characteristics and stability . Different examples can be mentioned concerning the load, release, biocompatibility and bactericide effect of these common biocides in both new and commercial biodegradable polymers.…”
Section: Introductionmentioning
confidence: 99%